Economics and Finance. - Albery, Michael; Henderson, John S. (The Accounting Review, 1957)
Reviews two books on accounts. "Investissements, Rentabilite et Progres Technique," Guy Hosmalin; "Economic Analysis," by Edmund Whittaker.